2023
DOI: 10.3389/fmicb.2023.1213143
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of the benzimidazoles oxfendazole and flubendazole against Litomosoides sigmodontis is dependent on the adaptive and innate immune system

Abstract: Filarial nematodes can cause debilitating diseases such as lymphatic filariasis and onchocerciasis. Oxfendazole (OXF) is one promising macrofilaricidal candidate with improved oral availability compared to flubendazole (FBZ), and OXF is currently under preparation for phase 2 clinical trials in filariasis patients. This study aimed to investigate the immune system’s role during treatment with OXF and FBZ and explore the potential to boost the treatment efficacy via stimulation of the immune system. Wild type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Similarly, oxfendazole is a drug that is used against intestinal helminths in the veterinary field over several decades. In vitro and in vivo animal studies showed that oxfendazole is also active against filarial nematodes [ 27 , 28 ]. Oxfendazole was tested in Phase 1 clinical trials [ 29 ] and will be tested in onchocerciasis, loiasis, mansonellosis and Trichuris trichiura patients in a Phase 2 clinical basket trial [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, oxfendazole is a drug that is used against intestinal helminths in the veterinary field over several decades. In vitro and in vivo animal studies showed that oxfendazole is also active against filarial nematodes [ 27 , 28 ]. Oxfendazole was tested in Phase 1 clinical trials [ 29 ] and will be tested in onchocerciasis, loiasis, mansonellosis and Trichuris trichiura patients in a Phase 2 clinical basket trial [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies in Mexico demonstrated that flubendazole has high macrofilaricidal activity [ 33 , 34 ] and in vivo laboratory studies confirmed this activity [ 35 ]. Recently, the important role of the immune system in supporting the macrofilaricidal efficacy for the related drug oxfendazole was demonstrated in the Litomosoides sigmodontis filarial mouse model [ 28 ]. Despite the limitation that some candidates may require an intact immune system for efficacy, several promising candidates were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Upon combining humanised dose exposures of ABZ equivalent to standard 400 mg dosing (Turner et al, 2017 ) or matching doses of the veterinary OXF, which has higher systemic exposure and is being repurposed for human helminth indications (Lanusse et al, 1995 ; Gokbulut et al, 2007 ; Bach et al, 2020 ; Ehrens et al, 2022 ; Risch et al, 2023 ), we could demonstrate a pharmacological synergy of otherwise sub-optimal doses of AWZ1066S given alone for 5 days. The impact of ABZ “rescue” meant these otherwise ~2-fold sub-optimal 5-day doses could recapitulate profound sterilising and partial macrofilaricidal activities in the rodent models and washout periods tested.…”
Section: Discussionmentioning
confidence: 99%
“…Embryogram from adult worms was done as described elsewhere (Ziewer et al, 2012 ; Risch et al, 2023 ). Briefly, worms were fixed using 4% formaldehyde for 24 h and then stored in 60% ethanol until analysis.…”
Section: Methodsmentioning
confidence: 99%